2010
DOI: 10.1021/jz1011143
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Deoxygenation of Graphite Oxide with Laser Excitation in Solution and Graphene-Aided Increase in Water Temperature

Abstract: We report the development of a facile laser reduction method for the synthesis of laser converted graphene (LCG) from graphite oxide (GO). The method provides a solution processable synthesis of individual graphene sheets in water under ambient conditions without the use of any chemical reducing agent. We also report on the high performance of GO and LCG for the efficient conversion of the laser radiation into usable heat, particularly for heating water for a variety of potential thermal, thermochemical, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
245
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(260 citation statements)
references
References 38 publications
13
245
2
Order By: Relevance
“…Other methods have been reported with the same phenomenon but with different light sources, such as UV or xenon flash [73,74], or different kinds of lasers, such as femtosecond laser, pulsed laser, etc. [75][76][77][78][79]. In addition, Zhou et al have reported a method to selectively reduce GO by laser writing [80].…”
Section: Radiation Based Methodsmentioning
confidence: 99%
“…Other methods have been reported with the same phenomenon but with different light sources, such as UV or xenon flash [73,74], or different kinds of lasers, such as femtosecond laser, pulsed laser, etc. [75][76][77][78][79]. In addition, Zhou et al have reported a method to selectively reduce GO by laser writing [80].…”
Section: Radiation Based Methodsmentioning
confidence: 99%
“…[106][107][108][109][110][111][112][113] Because of the high energy per unit pulse of the light, the bonds between the graphene sheet and the oxygen functionalities in GO can be destroyed to produce RGO with relatively less impurity. Moreover, this method can be exploited for nanopatterning and for large-scale production of reduced graphene oxide.…”
Section: Photoreductionmentioning
confidence: 99%
“…Moreover, this method can be exploited for nanopatterning and for large-scale production of reduced graphene oxide. Abdelsayed et al [111] employed a facile laser reduction method for preparing graphene from GO, and such effects of laser irradiation were associated with thermal effects. With the increasing of laser irradiation time, the temperature of the GO solution increased and the yellow golden color of the GO solution changed gradually to brown and finally to black, which indicated the deoxygenation of GO.…”
Section: Photoreductionmentioning
confidence: 99%
“…GO can be successively reduced to graphene by the partial restoration of the sp 2 -hybridization by thermal [127], chemical [128], electrochemical [129], photothermal [130], Catalysts 2017, 7, 305 6 of 34 photocatalytic [69,131], sonochemical [132,133], and microwave reduction methods [134]. The high number of oxygen-containing groups of the obtained GO product permits the interaction with the cations, providing important reactive molecules for the nucleation and growth of nanoparticles and therefore the formation of various graphene-based composites.…”
Section: Introductionmentioning
confidence: 99%